Pharmacokinetics and Pharmacodynamics of Tofogliflozin (a Selective SGLT2 Inhibitor) in Healthy Male Subjects - Kasahara-Ito, Nahoko; Fukase, Hiroyuki; Ogama, Yoichiro; Saito, Tomohisa; Ohba, Yasuhiro; Shimada, Sumire; Takano, Yasuki; Ichihara, Tomoko; Terao, Kimio; Nakamichi, Noboru; Kumagai, Yuji; Ikeda, Sachiya (Drug Research, 2017)
Tofogliflozin is a selective oral inhibitor of sodium-glucose co-transporter 2 for treatment of type 2 diabetes mellitus. The pharmacokinetics, pharmacodynamics, and safety of tofogliflozin were investigated in healthy male subjects. Three studies were conducted: single-ascending dose study (10–640 mg) in 56 Japanese and 24 Caucasian subjects; multiple-ascending dose study (2.5–80 mg once daily for 7 days) in 24 Japanese subjects; and food-effect study (20–40 mg) in 30 Japanese subjects. Tofogliflozin was absorbed rapidly and eliminated from the systemic circulation with a t1/2 of 5–6 h. Exposure increased dose-proportionally up to 320 mg. Body weight-corrected exposure was similar between Japanese and Caucasian subjects. Urinary excretion of tofogliflozin ranged from 17.1 to 27.4% of dose. Tofogliflozin did not accumulate with once daily administration. Food intake decreased Cmax by approximately 30% but did not change AUC0-inf. Tofogliflozin caused dose-dependent daily urinary glucose excretion (UGE0-24h), but food intake condition at administration did not affect it. The exposure-response relationship between plasma average concentration of tofogliflozin (Cavg) and UGE0-24h fitted Emax model well. There were no serious adverse events leading to discontinuation or episodes of hypoglycemia. Single and multiple administration of tofogliflozin were generally well tolerated. Exposure to tofogliflozin was dose-proportional up to 320 mg and did not accumulate with multiple once-a-day administration. The model suggests more than 100 ng/mL Cavg corresponding to the dose of between 20 and 40 mg leads to almost maximum effect of tofogliflozin.
Keywords: tofogliflozin; healthy male subject; Japanese and Caucasian; food effect; urinary glucose excretion; type 2 diabetes mellitus